Functional Characterization of the Small Regulatory Subunit PetP from the Cytochrome b6f Complex in Thermosynechococcus elongatus . Issue 8 (19th August 2014) - Rexroth, Sascha; Rexroth, Dorothea; Veit, Sebastian; Plohnke, Nicole; Cormann, Kai U.; Nowaczyk, Marc M.; Rögner, Matthias
Abstract : Successful isolation of a highly active b6 f complex including the PetP subunit allowed detailed analysis of the function of this recently discovered subunit. PetP appears to promote the stability and activity of the b6 f complex and to influence linear electron transport. Abstract: The cyanobacterial cytochrome b6 f complex is central for the coordination of photosynthetic and respiratory electron transport and also for the balance between linear and cyclic electron transport. The development of a purification strategy for a highly active dimeric b6 f complex from the thermophilic cyanobacterium Thermosynechococcus elongatus BP-1 enabled characterization of the structural and functional role of the small subunit PetP in this complex. Moreover, the efficient transformability of this strain allowed the generation of a ΔpetP mutant. Analysis on the whole-cell level by growth curves, photosystem II light saturation curves, and P700 + reduction kinetics indicate a strong decrease in the linear electron transport in the mutant strain versus the wild type, while the cyclic electron transport via photosystem I and cytochrome b6 f is largely unaffected. This reduction in linear electron transport is accompanied by a strongly decreased stability and activity of the isolated ΔpetP complex in comparison with the dimeric wild-type complex, which binds two PetP subunits. The distinct behavior of linear and cyclic electron transport may suggest the presence of two distinguishable pools of cytochrome b6 f complexes with different functions that might be correlated with supercomplex formation.